Pengaruh Key Opinion Leader dan Electronic Word of Mouth Terhadap Keputusan Pembelian Smartphone Samsung Galaxy Seri A di Kota Banjarmasin - Noor Endah Saputri; Taharuddin; Rizki Muslim Hidayat; Devi Rusvitawati (Business Administration, FISIP ULM, 2026)
Key Opinion Leaders and electronic Word of Mouth among smartphone users in Banjarmasin City serve as supporting factors that influence purchasing decisions for Samsung Galaxy A Series smartphones. The purpose of this research is to analyze and determine both the partial and simultaneous effects of Key Opinion Leaders and electronic Word of Mouth on purchasing decisions for Samsung Galaxy A Series smartphones in Banjarmasin City. This research is conducted using a quantitative method and was conducted in Banjarmasin City. This study involved 100 respondents selected through purposive sampling who had purchased a Samsung Galaxy A Series smartphone and previously watched technology review content from a Key Opinion Leader. Primary data were collected through questionnaires, and hypothesis testing was conducted using Multiple Linear Regression Analysis with SPSS version 31 as the analytical tool. The findings showed that Key Opinion Leaders and Electronic Word of Mouth was found to have a positive and significant partial effect as well as a simultaneous influence on purchasing decisions for Samsung Galaxy A Series smartphones in Banjarmasin City. These results suggest that leveraging credible technology reviewers and managing digital consumer reviews can effectively strengthen consumers’ purchasing decisions toward Samsung Galaxy A Series smartphones.